Pengembangan Media Buku Cerita Bergambar Untuk Meningkatkan Pemahaman Anak Tentang Mitigasi Bencana - Melina Yuli Kartika; Vit Ardhyantama; Urip Tisngati (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
This research aims to develop a picture storybook to increase childrens’ understanding about earthquake and tsunami disaster mitigation. This type of research is Research and Development (R&D) with the ADDIE development model which consists of five stages, namely, analysis, design, development, implementation, and evaluation. The data collection techniques used were observation, tests, questionnaires, and documentation. The data analysis technique used is the analysis of the level of validity of the product and the data analysis of the test results with paired sample t tests. The results showed that: (1) the earthquake and tsunami disaster mitigation picture storybook media has been developed using the ADDIE model, (2) the picture storybook media is declared "Very Valid" based on the average media expert assessment of 4.5, the average material expert assessment of 5, and the average linguist assessment of 4.36, (3) the development results show that children's responses to picture storybook media are very positive with an average small group response questionnaire of 4.71 (Very Valid) and an average large group response questionnaire of 4.38 (Very Valid); (4) the picture storybook media is declared effective in increasing children's understanding of earthquake and tsunami disaster mitigation with the results of the t test sig. (2-tailed) 0.004 < 0.05.